The role of Computer-Assisted Translation in the field of software localization - Fernández Costales, Alberto (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article analyses the effectiveness of computer-assisted translation (CAT) in the field of software localization. In order to measure and assessthe advantages of using translation tools, a program is localized using Passolo, a specialized software localization application. The study is intendedto calibrate how CAT can improve translators’ performance in a localization project and also to appraise the main features of the selectedapplication, focusing on functionality, usability and reliability. The article outlines some of the challenges and difficulties of software localization,aiming to test how the process of adapting a product to a particular locale can be optimized by the use of computer assisted translation. The casestudy focuses on the main challenges of the process from the point of view of translation. To conclude, the study formulates a number of conclusionsand evaluates the performance of the selected application.